Hepatocyte growth factor measurement in AL amyloidosis. (June 2015) - Abraham, Julie; Desport, Estelle; Rigaud, Charlotte; Marin, Benoit; Bender, Sébastien; Lacombe, Corinne; Moreau, Stéphane; Yagoubi, Fatima; Bordessoule, Dominique; Lavergne, David; Bridoux, Frank; Jaccard, Arnaud
Abstract Hepatocyte growth factor (HGF) is a pro-angiogenic cytokine activated by tissue-type plasminogen activator (tPA) that might play a role in the progression of multiple myeloma (MM). Preliminary studies indicated that serum HGF levels were higher in patients with AL amyloidosis (AL) compared to those with MM. The aim of the present study was to determine whether HGF is a relevant marker of diagnosis and prognosis in AL. HGF serum levels were measured at diagnosis in patients with monoclonal gammopathy (MG) without AL (76 controls), or with biopsy-proven systemic AL (69 patients). HGF serum levels were significantly higher in patients with AL compared to controls, respectively, 11.2 ng/mL [min: 0.95–max: 200.4] versus 1.4 ng/mL [min: 0.82–max: 6.2] (p < 0.0001). The threshold value of 2.2 ng/mL conferred optimal sensitivity (88%) and specificity (95%) to differentiate AL and monoclonal gammopathy of undetermined significance (MGUS) patients. Serum HGF concentrations were correlated positively with the severity of cardiac involvement and the serum level of monoclonal light chains. These data suggest that HGF measurement could be used in patients with MG to detect AL or to reinforce a clinical suspicion of AL and to guide indications for diagnostic tissue biopsies.